Perancangan Struktur Apartement 20 Lantai Bandar Lampung - Alim, Fauzil; Bayzoni, Bayzoni; Husni, Hasti Riakara (Universitas Lampung, 2015)
Bandar Lampung is one of the cities in Indonesia, which is being developed at this time. Thesedevelopments will affect population and workforce. The flurry will make the work of the public donot have much free time to prepare for daily needs. Condition, situation, and the state of society asthis causes them to prefer a place that provides various kinds of necessities of life (one stopservice).This apartment structure design project at the Teluk Betung which consists of 20 floors has 620rooms with various types and consists of Type A (230 m2), Type B (152 m 2 ), Type C (135 m 2 ), TypeD (120 m 2 ), Type E (98 m 2 ), Type F (73 m 2 ) and Type G (54 m 2 ). The apartment is also equippedwith various facilities such as a cafeteria, mini market, restaurant, fitness room, a mosque and amultipurpose hall.To analyze the structure, ETABS Non Linear version 9.7.4 software are used to get internal forcesand will be used in manually design of reinforce concrete refer to Concrete SNI code 03-2847-2002 and Earthquake code SNI 03-1726-2002. To compare the result Sp Coloum v. 4.81. and RC.Beam Design V.1.0. are used. The calculation obtained 80 x 80 cm coloum with 24 D 25reinforcement, 35 x 60 cm primary beam and 15 x 30 cm secondary beam. The pile pondation areused for pondation with 9 pile pondation, 60 cm diameter and 18 m depth.Key words: Structure, ETABS, Pile Pondation